The Effectiveness of Repetition Drill Technique To Improve Electrical Engineering Student’s Speaking Skill - Widianingsih, Betti; Syafirullah, Lutfi; Guilin, Xie; Jiao, Deng; Wang, Yuanyuan (Journal International of Lingua and Technology, 2023)
The purpose of this study is to investigate how effective the repetition drill technique is in improving the speaking ability of the 2022–2023 Second Semester Electrical Engineering students at Cilacap State Polytechnic. The study was conducted using a classroom action research technique, and 23 students participated as study participants. A pretest was administered to find out what obstacles the students faced, and the average score was 39.67. Data were collected using an oral exam over three study cycles. The average score of the students in the first cycle, conducted on March 21, 2023, was 46.73. Next, the average score of the students for the second test conducted on March 22, 2023, was 67.93. On March 24, 2023, the average score for Cycle 3 students would be 82.06. The student's average score improves on rounds 1–3. The student's speaking ability improves gradually. This is confirmed by the post-test results obtained in the categories of 'good' and 'excellent' after 3 cycles of review exercises in English practice class. Students' pronunciation and language skills improves significantly. In summary, this study proved that repetition drill techniques can be used very effectively in English practice courses.